Contribution of Youth Livelihood Program (YLP) Towards Agriculture in Nyarusiza Sub-County Kisoro District. - Ndirahisha, Brian (Kabale University, 2024)
The study assessed the contribution of youth livelihood program (YLP) towards agriculture in Nyarusiza Sub-county Kisoro district, following the study objectives which were to assess the contributions of YLPs towards Agriculture development in Nyarusiza Sub-county, to identify the key challenges faced by youth entrepreneurs in accessing markets and sustaining their businesses under the YLP and to suggest possible strategies to the challenges faced by youth entrepreneurs in accessing markets and sustaining their businesses under the YLP. The study adopted a case study research design across a sample of 50 respondents. Data collection tools were interviews and questionnaires. The findings of the study revealed that female respondents were highly represented in the study and they were being supported by youth livelihood programs from different villages of Nyarusiza sub-county Kisoro district. The study concluded that the Youth Livelihood Programme (YLP) has made notable contributions to agricultural development in Nyarusiza Sub-County, Kisoro District. However, several challenges hinder its full potential. Addressing these challenges through targeted strategies can enhance the program's effectiveness, leading to greater agricultural productivity, economic growth, and youth empowerment. By integrating these findings with broader research insights, it becomes clear that a comprehensive approach involving financial support, capacity building, market access, and coordinated efforts among stakeholders is essential for achieving sustainable agricultural development and empowering young farmers in the region. The study concluded that government should establish strong market connections which can help farmers achieve better prices and reduce market volatility and there should be provision of timely and accurate market data which can help farmers make informed decisions, reducing risks associated with market uncertainties.